Solder alloy, solder powder, solder paste, and solder joint

By adjusting the content of Ag, Cu and Bi, a solder alloy that satisfies the composition of a specific alloy is prepared, which solves the problems of high liquid phase temperature and low solid phase temperature in the prior art, and achieves the effects of high mountingability, strength and thermal fatigue resistance.

CN119747960APending Publication Date: 2025-04-04SENJU METAL IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510102123.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-03-10
Filing Date
2022-03-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the use of power semiconductor devices, it is difficult for the existing solder alloy to meet the requirements of low liquid phase temperature and not low solid phase temperature, resulting in insufficient mounting and thermal fatigue resistance.

Method used

By adjusting the content of Ag, Cu and Bi, a solder alloy with alloy composition meeting 10.9≤Sn/Bi≤22.4, 46.9≤Sn×Cu≤72.1 and 45.50≤Sn×Ag≤365 was prepared to ensure that the liquid phase line temperature is lower than 217°C and the solid phase line temperature is moderate.

Benefits of technology

The excellent mounting properties of the solder alloy, high tensile strength and significant improvement in the thermal fatigue resistance under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254455160000151
    Figure BDA0005254455160000151
  • Figure BDA0005254455160000161
    Figure BDA0005254455160000161
  • Figure HDA0005254455170000011
    Figure HDA0005254455170000011
Patent Text Reader

Abstract

Provided are a solder alloy, a solder powder, a solder paste, and a soldered joint, which have excellent mountability due to a low liquidus temperature and not too low solidus temperature, and which exhibit high strength and excellent thermal fatigue resistance. The solder alloy has an alloy composition comprising, in mass%, 0.5-4.0% of Ag, more than 0.5% but 1.0% or less of Cu, more than 3.0% but 8.0% or less of Bi, and the remainder comprising Sn. The alloy composition preferably satisfies the following formulae (1)-(3). In formulae (1) to (3), Sn, Bi, Cu and Ag represent the content (mass%) of each alloy composition. 10.9 < = Sn / Bi < = 22.4 (1) Formula 46.9 < = Sn * Cu < = 72.1 (2) Formula 45.50 < = Sn * Ag < = 365 (3) Formula.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of March 10, 2022, application number 202210228779.7, and invention name “Solder alloy, solder powder, solder paste and solder joint”. Technical Field

[0002] The present invention relates to a solder alloy, a solder powder, a solder paste and a solder joint having excellent reliability. Background Art

[0003] The power semiconductor device is a structure in which a plurality of elements and electrode terminals (external connection terminals) are connected to an insulating substrate (hereinafter referred to as "DCB (Direct Copper Bonding)") on which a copper circuit is formed. To form the power semiconductor device, for example, step soldering is used, in which the elements and external connection terminals are soldered sequentially.

[0004] When multi-stage soldering is performed by step soldering, an alloy composition having a liquidus temperature lower than the solidus temperature of the solder alloy used in the initial soldering is selected for the solder alloy used for the second soldering. As alloy compositions having low liquidus temperatures and melting points, for example, Sn-Ag-Cu-Bi solder alloys are disclosed in Patent Documents 1 to 3. In the invention described in Patent Document 2, there is a concern that the solder joint may break when external stress is applied to the external connection terminal, so a Sn-Ag-Cu-Bi solder alloy is disclosed that has high strength itself and exhibits high bonding strength at room temperature.

[0005] On the other hand, some Sn-Ag-Cu-Bi solder alloys are designed to withstand severe use environments. For example, Patent Document 3 discloses a Sn-Ag-Cu-Bi solder alloy having high bonding strength after thermal cycling.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2-70033

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 2004-122223

[0010] Patent Document 3: Japanese Patent Application Publication No. 2019-155466 Summary of the invention

[0011] Problem that the invention aims to solve

[0012] Here, under the normal use of power semiconductor devices, it is difficult to imagine that stress will be directly applied to the components of the power semiconductor device from the outside. Therefore, the solder alloy used to connect the components to the DCB can be the Sn-3Ag-0.5Cu solder alloy that has been widely used (hereinafter, the unit of the numerical value marked before the element symbol is "mass %"). When manufacturing power semiconductor devices using step soldering, the external connection terminals are usually connected immediately after the components. Therefore, it is expected that the liquidus temperature of the solder alloy connecting the external connection terminals is lower than the solidus temperature of the above-mentioned solder alloy, which is 217°C.

[0013] The solder alloy disclosed in Patent Document 1 forms a paste that has neither liquid fluidity nor solid hardness in the temperature range between the liquidus temperature and the solidus temperature, and has good mechanical strength. Specifically, Patent Document 1 discloses a Sn-0.4Ag-0.2Cu-6Bi solder alloy. The solder alloy disclosed in Patent Document 2 is an alloy composition in which Cu and Ag satisfy a prescribed relationship, and is designed to suppress Ag corrosion without destroying the bonding strength. Specifically, Patent Document 2 discloses a Sn-3.2Ag-0.8Cu-5Bi solder alloy. The inventions described in Patent Documents 1 and 2 preferably have a low liquidus temperature, but no alloy design that can be applied to step soldering has been performed, so it is difficult to say that the liquidus temperatures of these solder alloys are sufficiently low.

[0014] Furthermore, in these inventions, the corrosion, dislocation, reoxidation, voids and other installation properties of the components are not studied, so even if the solidus temperature is low and the temperature range with the liquidus temperature is wide, it does not become a problem. In particular, as described above, Patent Document 1 describes that good mechanical properties are exhibited in the temperature range between the liquidus temperature and the solidus temperature, so in the invention described in this document, the wide temperature range is more preferred.

[0015] In addition, since the external electrode terminals used in the power semiconductor device are connected to external electrodes, when tensile stress is repeatedly applied to the external electrode terminals from the outside, the applied stress will be concentrated on the solder joint connecting the DCB and the external electrode terminals. Furthermore, the power semiconductor device sometimes reaches about 125°C during operation. The solder alloy used in the power semiconductor device needs to have excellent thermal fatigue resistance that will not deteriorate even if it is exposed to such a high temperature environment for a long time.

[0016] The invention disclosed in Patent Document 3 is an excellent invention that can show high bonding strength after thermal cycling by focusing on the behavior of Bi during thermal cycling. As a specific alloy composition, for example, a solder alloy of Sn-3.3Ag-0.9Cu-5.0Bi is disclosed. Although Patent Document 3 states that in order to suppress thermal damage to the printed circuit board, the liquidus temperature is preferably below 235°C, similar to the inventions described in Patent Documents 1 and 2, an alloy design that can be applied to step soldering is not performed. Therefore, it is difficult to say that the liquidus temperature of the above-mentioned solder alloy is sufficiently low. In addition, in the invention described in Patent Document 3, although a high bonding strength after thermal cycling is obtained, an alloy design that improves the heat fatigue resistance is not performed. This is also the same as the inventions described in Patent Documents 1 and 2.

[0017] Thus, even if the solder alloys described in Patent Documents 1 and 2 can solve their respective problems, it is difficult to say that they can solve various problems related to power semiconductor devices because, for example, the actual conditions during the manufacture and use of power semiconductor devices are not taken into consideration. In the solder alloy described in Patent Document 3, there is room for improvement in these aspects. In addition, for solder alloys, although each element has an inherent meaning of addition, the solder alloy is a material that is a combination of all constituent elements, and each constituent element will affect each other. Therefore, in order to simultaneously solve various problems related to power semiconductor devices, each constituent element must be contained in a well-balanced manner as a whole. In order to provide a solder alloy that can simultaneously solve all of the above-mentioned problems, further exploration of the composition is essential.

[0018] Therefore, an object of the present invention is to provide a solder alloy, solder powder, solder paste and solder joint which are excellent in mountability due to a low liquidus temperature and a not excessively low solidus temperature, exhibit high strength and are excellent in thermal fatigue resistance.

[0019] Solutions for solving problems

[0020] The present inventors investigated the contents of each constituent element in the solder alloy disclosed in the patent document in such a way that the liquidus temperature is lower than the solidus temperature of the Sn-3Ag-0.5Cu solder alloy. In the Sn-0.4Ag-0.2Cu-6Bi solder alloy described in Patent Document 1, it was found that the contents of Ag and Cu are small and the liquidus temperature is high. In the Sn-3.2Ag-0.8Cu-5Bi solder alloy described in Patent Document 2, it was found that the content of Cu is large and the liquidus temperature is high. In the Sn-3.3Ag-0.9Cu-5.0Bi solder alloy described in Patent Document 3, it was found that the content of Cu is large and the liquidus temperature is high.

[0021] Based on these insights, the alloy composition was investigated in a manner to reduce the liquidus temperature, and the result was that the desired liquidus temperature would be shown when the content of each constituent element was within the specified range. However, it was recognized that even if the alloy composition was within the obtained range, there was a solder alloy with an alloy composition having low tensile strength and an alloy composition whose heat fatigue resistance under a high temperature environment did not reach the desired value. Therefore, considering the overall balance, the content of each constituent element was further investigated in detail within the above range. As a result, the following insights were obtained: when the content of each constituent element was within a specific range, the liquidus temperature was low enough to be used for the second soldering of step soldering and the solidus temperature was not too low, the mountability was excellent, the tensile strength was high, and the heat fatigue resistance under a high temperature environment was improved dramatically. In addition, in the present invention, although a power semiconductor device is exemplified, it is not limited to this as long as the use of a solder alloy that requires a low liquidus temperature and a solidus temperature that is not too low, high strength, and high heat fatigue resistance is required.

[0022] The present invention obtained based on these findings is as follows.

[0023] (1) A solder alloy characterized by having an alloy composition of, in mass %, 2.0 to 4.0% Ag, 0.51 to 0.79% Cu, more than 4.0% and less than 8.0% Bi, and the balance being Sn, wherein the solder alloy has a liquidus temperature of less than 217°C.

[0024] (2) The solder alloy according to (1) above, wherein the alloy composition satisfies the following formulas (1) to (3).

[0025] 10.9≤Sn / Bi≤22.4 (1)

[0026] 46.9≤Sn×Cu≤72.1 (2)

[0027] 45.50≤Sn×Ag≤365 (3)

[0028] In the above formulas (1) to (3), Sn, Bi, Cu and Ag represent the contents (mass %) of the respective alloy compositions.

[0029] (3) A solder powder comprising the solder alloy described in (1) or (2) above.

[0030] (4) A solder paste comprising the solder powder according to (3) above.

[0031] (5) A solder joint comprising the solder alloy described in (1) or (2) above. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram showing the test method of the repeated tensile test. DETAILED DESCRIPTION

[0033] The present invention will be described in more detail below. In the present specification, "%" referring to the composition of the solder alloy means "mass %" unless otherwise specified.

[0034] 1. Solder alloy

[0035] (1) Ag: 0.5-4.0%

[0036] Ag can achieve precipitation strengthening of the solder alloy by causing Ag3Sn to precipitate in granular form. In addition, if the contents of Ag and Cu are both close to the SnAgCu eutectic composition, the liquidus temperature of the solder alloy can be reduced. If the Ag content is less than 0.5%, the liquidus temperature of the solder alloy will rise due to the SnAgCu hypoeutectic. In addition, the amount of compound precipitation is small and the strength is not improved. The lower limit of the Ag content is 0.5% or more, preferably 1.0% or more, and more preferably 2.0% or more.

[0037] On the other hand, if the Ag content is too much, the liquidus temperature of the solder alloy will rise due to the SnAgCu hypereutectic. In addition, coarse Ag3Sn will precipitate in a plate shape, deteriorating the strength. The upper limit of the Ag content is 4.0% or less, preferably 3.9% or less, more preferably 3.5% or less, and further preferably 3.0% or less.

[0038] (2) Cu: more than 0.5% and less than 0.8%

[0039] Cu can achieve precipitation strengthening of the solder alloy by precipitating Cu3Sn and Cu6Sn5. In addition, if the contents of Cu and Ag are both close to the SnAgCu eutectic composition, the liquidus temperature of the solder alloy can be reduced. If the Cu content is less than 0.5%, the liquidus temperature of the solder alloy will rise due to the SnAgCu hypoeutectic. In addition, the amount of compound precipitation is small and the strength is not fully improved. The lower limit of the Cu content exceeds 0.5%, preferably 0.51% or more, and more preferably 0.6% or more.

[0040] On the other hand, if the Cu content is too high, the liquidus temperature of the solder alloy increases due to the SnAgCu hypereutectic. The upper limit of the Cu content is less than 0.8%, preferably 0.79% or less, more preferably 0.75% or less, and further preferably 0.7% or less.

[0041] (3) Bi: more than 4.0% and less than 8.0%

[0042] Bi can improve the strength of the solder alloy by solid solution strengthening of Sn. In addition, Bi can also maintain the solid solution strengthening of Sn in a high temperature environment of about 125°C of the solder alloy. Therefore, in a high temperature environment, even if the SnAg compound and the SnCu compound become coarse, Sn maintains the solid solution strengthening based on Bi, so that the solder alloy can show high thermal fatigue resistance.

[0043] If the Bi content is too low, the amount of Bi dissolved in the solder is small, and the strength is not sufficiently improved. In addition, the liquidus temperature of the solder alloy does not decrease. The lower limit of the Bi content is more than 4.0%, preferably 4.1% or more, and more preferably 4.5% or more.

[0044] On the other hand, if Bi is added excessively, the SnBi eutectic precipitates and the solidus temperature drops, and the temperature range with the liquidus temperature widens, thereby reducing the corrosion, dislocation, reoxidation, voids and other installation properties of the components. In particular, when the Ag content is high, if the Bi content increases, the solidus temperature drops significantly. In addition, if the solidus temperature is low, it will be close to the temperature used to evaluate the heat fatigue resistance, so the solidus temperature is preferably a high temperature. Furthermore, Bi will segregate in the grain boundaries, and sometimes the strength and heat fatigue resistance of the solder alloy will be reduced. The upper limit of the Bi content is 8.0% or less, preferably 7.9% or less, more preferably 7.0% or less, further preferably 6.0% or less, and particularly preferably 5.0% or less.

[0045] (4) Residue: Sn

[0046] The solder alloy of the present invention has a balance of Sn. In addition to the aforementioned elements, the solder alloy may further contain inevitable impurities. Even if the inevitable impurities are contained, the aforementioned effects will not be affected.

[0047] (5) Formula (1) to Formula (3)

[0048] 10.9≤Sn / Bi≤22.4 (1)

[0049] 46.9≤Sn×Cu≤72.1 (2)

[0050] 45.50≤Sn×Ag≤365 (3)

[0051] In the above formulas (1) to (3), Sn, Bi, Cu and Ag represent the contents (mass %) of the respective alloy compositions.

[0052] The solder alloy of the present invention preferably satisfies equations (1) to (3). By satisfying equations (1) to (3), the balance of the contents of Ag, Cu and Bi is optimized, so that high strength and heat fatigue resistance can be exhibited while keeping the liquidus temperature low.

[0053] In more detail, in the solder alloy of the present invention, the solder alloy satisfying formula (1) to formula (3) is close to the SnAgCu eutectic composition, so the liquidus temperature is reduced. In addition, according to formula (1) to formula (3), it is inferred that the values ​​of each formula representing the balance between the content of each constituent element and the content of Sn are within a specified range, and the homogenization of the alloy structure caused by each constituent element can be achieved. Therefore, the strength and heat fatigue resistance of the solder alloy are further improved. In addition, the solidus temperature and the liquidus temperature fall into a more appropriate temperature range.

[0054] The above formula is obtained by the mutual dependence of each constituent element. This is because an alloy is a material that is formed by combining all constituent elements, and each constituent element affects each other.

[0055] Formula (1) is a relationship between the liquidus temperature and the solidus temperature caused by the solid solution strengthening of Sn. It is speculated that when formula (1) is satisfied, since Sn maintains high strength in a high temperature environment, fracture can be suppressed even in repeated tensile tests. In addition, the addition of Bi can achieve a lower liquidus temperature, and by satisfying formula (1), the extremely low temperature of the solidus temperature can be suppressed. Formulas (2) and (3) are relationship formulas caused by the precipitation amount of each SnAg compound and SnCu compound. The melting temperature of the SnAgCu solder alloy varies according to the content of Ag and Cu, and the liquidus temperature is lowered by the addition of Bi. Since there is an optimal content of each constituent element based on step soldering, formulas (1) to (3) are set to a range that fully considers the mutual dependence of each constituent element.

[0056] The lower limit of formula (1) is preferably 10.9 or more, more preferably 11.5 or more, further preferably 18.1 or more, and particularly preferably 18.2 or more. The upper limit of formula (1) is preferably 22.4 or less, more preferably 18.5 or less, and particularly preferably 18.3 or less.

[0057] The lower limit of formula (2) is preferably 46.9 or more, more preferably 61.2 or more, further preferably 63.2 or more, and particularly preferably 63.6 or more. The upper limit of formula (2) is preferably 72.1 or less, more preferably 64.6 or less, and further preferably 64.5 or less.

[0058] The lower limit of formula (3) is preferably 45.50 or more, more preferably 100.0 or more, further preferably 184.6 or more, and particularly preferably 273.6 or more. The upper limit of formula (3) is preferably 365 or less, more preferably 361.2 or less, further preferably 340.9 or less, further more preferably 276.6 or less, most preferably 274.5 or less, and particularly preferably 273.9 or less.

[0059] (6) Liquidus temperature and solidus temperature of solder alloy

[0060] The solder alloy of the present invention is preferably used for the second soldering when performing soldering twice, for example, by step soldering. In such a use, the liquidus temperature of the solder alloy used for the second soldering is preferably lower than the solidus temperature of the solder alloy used for the first soldering. For example, when a Sn-3Ag-0.5Cu solder alloy is used for the first soldering, the liquidus temperature of the solder alloy of the present invention is preferably lower than 217°C, more preferably below 215°C, and particularly preferably below 210°C.

[0061] The solidus temperature of the solder alloy of the present invention is preferably a temperature range in which the temperature difference between the liquidus temperature and the solidus temperature is not too large, and the mounting properties of the components such as corrosion, dislocation, reoxidation, and voids are not reduced. In addition, it is preferred that the temperature difference with the temperature used to evaluate the thermal fatigue resistance is large. The solidus temperature of the solder alloy of the present invention is preferably 150°C or more, more preferably 170°C or more, further preferably 187°C or more, and particularly preferably 197°C or more.

[0062] 2. Solder powder

[0063] The solder powder of the present invention is used for the solder paste described below, and is preferably a spherical powder. The fluidity is improved by being a spherical powder. The solder powder of the present invention preferably meets the size (particle size distribution) of numbers 1 to 8 in the classification of powder size in JIS Z 3284-1:2014 (Table 2). It is more preferred to meet the size (particle size distribution) of numbers 4 to 8, and it is further preferred to meet the size (particle size distribution) of numbers 5 to 8. If the particle size meets this condition, the surface area of ​​the powder will not be too large, and the increase in viscosity will be suppressed. In addition, the aggregation of fine powders is suppressed, and the increase in viscosity is sometimes suppressed. Therefore, soldering of finer components becomes possible.

[0064] The sphericity of the solder powder is preferably above 0.90, more preferably above 0.95, and most preferably above 0.99. In the present invention, the sphericity of the spherical powder is measured using a CNC image measuring system (ULTRA QUICK VISION ULTRA QV350-PRO measuring device manufactured by Mitutoyo) using the minimum zone center method (MZC method). In the present invention, the sphericity represents the degree of deviation from a sphere, for example, the arithmetic mean calculated when the diameter of 500 spheres is divided by the major diameter, and the closer the value is to the upper limit of 1.00, the closer it is to a sphere.

[0065] 3. Solder paste

[0066] The solder paste of the present invention contains the above-mentioned solder powder and flux.

[0067] (1) Flux composition

[0068] The flux used in the solder paste is composed of any one of organic acids, amines, amine hydrohalides, organic halogen compounds, thixotropic agents, rosin, solvents, surfactants, polymer compounds, silane coupling agents, and colorants, or a combination of two or more thereof.

[0069] Examples of the organic acid include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dimer acid, propionic acid, 2,2-bishydroxymethylpropionic acid, tartaric acid, malic acid, glycolic acid, diglycolic acid, thioglycolic acid, dithioglycolic acid, stearic acid, 12-hydroxystearic acid, palmitic acid, and oleic acid.

[0070] Examples of the amine include ethylamine, triethylamine, ethylenediamine, triethylenetetramine, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1' )]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, 2,4-diamino -6-vinyl-s-triazine, 2,4-diamino-6-vinyl-s-triazine isocyanuric acid adduct, 2,4-diamino-6-methacryloyloxyethyl-s-triazine, epoxy-imidazole adduct, 2-methylbenzimidazole, 2-octylbenzimidazole, 2-pentylbenzimidazole, 2-(1-ethylpentyl)benzimidazole, 2-nonylbenzimidazole, 2-(4-thiazolyl)benzimidazole, benzimidazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol], 6-(2-benzotriazolyl)-4-tert-octyl-6'-tert-butyl-4'-methyl-2,2'-methylenebisphenol, 1,2,3-benzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]benzotriazole, carboxybenzotriazole, 1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole, 2,2'-[[(methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol, 1-(1',2'-dicarboxyethyl)benzotriazole, 1-(2,3-dicarboxypropyl)benzotriazole, 1-[(2-ethylhexylamino)methyl]benzotriazole, 2,6-Bis[(1H-benzotriazol-1-yl)methyl]-4-methylphenol, 5-methylbenzotriazole, 5-phenyltetrazolyl, etc.

[0071] Amine hydrohalides are compounds obtained by reacting amines with hydrogen halides. Examples of amines include ethylamine, ethylenediamine, triethylamine, diphenylguanidine, ditolylguanidine, methylimidazole, 2-ethyl-4-methylimidazole, and the like. Examples of hydrogen halides include hydrides of chlorine, bromine, and iodine. Examples of amine hydrohalides include amine trifluoride boron complex salts and amine tetrafluoroborate. Examples of amine trifluoride boron complex salts include piperidine trifluoride boron complex salts and amine tetrafluoroborate, such as cyclohexylamine tetrafluoroborate and dicyclohexylamine tetrafluoroborate.

[0072] Examples of the organic halogen compound include trans-2,3-dibromo-2-butene-1,4-diol, triallyl isocyanurate hexabromide, 1-bromo-2-butanol, 1-bromo-2-propanol, 3-bromo-1-propanol, 3-bromo-1,2-propanediol, 1,4-dibromo-2-butanol, 1,3-dibromo-2-propanol, 2,3-dibromo-1-propanol, 2,3-dibromo-1,4-butanediol, and 2,3-dibromo-2-butene-1,4-diol.

[0073] As the thixotropic agent, wax-based thixotropic agents, amide-based thixotropic agents, sorbitol-based thixotropic agents, etc. can be cited. As the wax-based thixotropic agent, for example, hydrogenated castor oil, etc. can be cited. As the amide-based thixotropic agent, monoamide-based thixotropic agents, bisamide-based thixotropic agents, and polyamide-based thixotropic agents can be cited. Specifically, lauramide, palmitamide, stearamide, behenamide, hydroxystearamide, saturated fatty acid amide, oleamide, erucamide, unsaturated fatty acid amide, p-toluene methane amide, aromatic amide, methylene bisstearamide, ethylene bislauramide, ethylene bishydroxystearamide, saturated fatty acid bisamide, methylene bisoleamide, unsaturated fatty acid bisamide, m-xylylene bisstearamide, aromatic bisamide, saturated fatty acid polyamide, unsaturated fatty acid polyamide, aromatic polyamide, substituted amide, hydroxymethyl stearamide, hydroxymethylamide, fatty acid ester amide, etc. can be cited. Examples of the sorbitol-based thixotropic agent include dibenzylidene-D-sorbitol and bis(4-methylbenzylidene)-D-sorbitol.

[0074] Examples of the surfactant include nonionic surfactants and weakly cationic surfactants.

[0075] Examples of the nonionic surfactant include polyoxyalkylene glycols, polyoxyalkylene alkyl ethers, polyoxyalkylene esters, polyoxyalkylene acetylene glycols, polyoxyalkylene alkyl amides, such as polyethylene glycol, polyethylene glycol-polypropylene glycol copolymers, aliphatic alcohol polyoxyethylene adducts, aromatic alcohol polyoxyethylene adducts, polyhydric alcohol polyoxyethylene adducts, polyoxyalkylene glyceryl ethers, and the like.

[0076] Examples of weak cationic surfactants include aliphatic amine polyoxyalkylene adducts, aromatic amine polyoxyalkylene adducts, and terminal diamine polyalkylene glycols, such as aliphatic amine polyoxyethylene adducts, aromatic amine polyoxyethylene adducts, polyamine polyoxyethylene adduct terminal diamine polyethylene glycol, and terminal diamine polyethylene glycol-polypropylene glycol copolymers.

[0077] As rosin, for example, raw rosin such as gum rosin, wood rosin and tall oil rosin, and derivatives obtained from the raw rosin can be cited. As the derivative, for example, purified rosin, hydrogenated rosin, disproportionated rosin, polymerized rosin and α, β unsaturated carboxylic acid modified products (acrylated rosin, maleated rosin, fumarated rosin, etc.), and the purified, hydrogenated and disproportionated products of the polymerized rosin, and the purified, hydrogenated and disproportionated products of the α, β unsaturated carboxylic acid modified products, etc., can be cited, and two or more kinds can be used. In addition, on the basis of the rosin-based resin, it can also include at least one or more resins selected from terpene resins, modified terpene resins, terpene phenolic resins, modified terpene phenolic resins, styrene resins, modified styrene resins, xylene resins and modified xylene resins. As modified terpene resins, aromatic modified terpene resins, hydrogenated terpene resins, hydrogenated aromatic modified terpene resins, etc. can be used. As modified terpene phenolic resins, hydrogenated terpene phenolic resins, etc. can be used. As the modified styrene resin, styrene acrylic resin, styrene maleic resin, etc. can be used. As the modified xylene resin, phenol-modified xylene resin, alkylphenol-modified xylene resin, phenol-modified resol type xylene resin, polyol-modified xylene resin, polyoxyethylene added xylene resin, etc. can be mentioned.

[0078] Examples of the solvent include water, alcohol solvents, glycol ether solvents, and pine alcohols. Examples of the alcohol solvent include isopropyl alcohol, 1,2-butanediol, isobornylcyclohexanol, 2,4-diethyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, 2,5-dimethyl-2,5-hexanediol, 2,5-dimethyl-3-hexyne-2,5-diol, 2,3-dimethyl-2,3-butanediol, 1,1,1-tris(hydroxymethyl)ethane, 2-ethyl-2-hydroxymethyl-1,3-propanediol, 2,2'-oxybis(oxy)propane 1,2,6-trihydroxyhexane, bis[2,2,2-tris(hydroxymethyl)ethyl]ether, 1-ethynyl-1-cyclohexanol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, erythritol, threitol, guaifenesin, 3,6-dimethyl-4-octyne-3,6-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, etc. Examples of the glycol ether solvent include diethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, 2-methylpentane-2,4-diol, diethylene glycol monohexyl ether, diethylene glycol dibutyl ether, and triethylene glycol monobutyl ether.

[0079] (2) Flux content

[0080] The content of the flux is preferably 5 to 95% and more preferably 5 to 15% based on the total mass of the solder paste. Within this range, the thickening suppression effect due to the solder powder can be fully exhibited.

[0081] (3) Method for manufacturing solder paste

[0082] The solder paste of the present invention can be manufactured by a general method in the art. First, the manufacture of solder powder can be carried out by the following well-known methods: a dropping method in which molten solder material is dripped to obtain particles, a spray method in which centrifugal spraying is performed, a method in which a block of solder material is crushed, etc. In the dropping method and the spray method, the dropping and spraying are preferably carried out in an inert atmosphere or a solvent in order to make particles. Then, the above-mentioned components are heated and mixed to prepare a flux, and the above-mentioned solder powder and, if necessary, zirconium oxide powder are introduced into the flux, and stirred and mixed to thereby manufacture.

[0083] 4. Brazing joints

[0084] The solder joint of the present invention is suitable for joining at least two or more joined members. The joined members are not particularly limited as long as they are components, substrates, electronic components, printed circuit boards, insulating substrates, semiconductors and power modules using electrode terminals, inverter products, etc., and are electrically connected using the solder alloy of the present invention.

[0085] 5. Others

[0086] The solder alloy of the present invention can be manufactured by using a low α radiation dose material as its raw material. If such a low α radiation dose alloy is used to form solder bumps around a memory, soft errors can be suppressed.

[0087] Example

[0088] The present invention will be described below with reference to the following examples, but the present invention is not limited to the following examples.

[0089] In order to demonstrate the effect of the present invention, the liquidus temperature, solidus temperature and tensile strength were measured using the solder alloys listed in Table 1. In addition, arbitrary examples and comparative examples were selected from Table 1 and their thermal fatigue resistance in a high temperature environment was evaluated.

[0090] (1) Liquidus temperature, solidus temperature

[0091] For the solder alloys having the alloy compositions listed in Table 1, the respective temperatures were determined from the DSC curves. The DSC curves were obtained by heating the solder alloys at 5°C / min in the atmosphere using a DSC (model: EXSTAR6000) manufactured by Hitachi High-Tech Science Corporation. The liquidus temperature and the solidus temperature were determined from the obtained DSC curves.

[0092] When the liquidus temperature is lower than 217°C, it is a temperature with no practical problem, so it is evaluated as "0", and when it is lower than 150°C and higher than 217°C, it is evaluated as "×". In addition, when the solidus temperature is higher than 150°C and lower than 217°C, it is a temperature with no practical problem, so it is evaluated as "0", and when it is higher than 217°C, it is evaluated as "×".

[0093] (2) Tensile strength

[0094] The tensile strength is measured according to JIS Z 3198-2. For each solder alloy described in Table 1, a test piece with a gauge length of 30 mm and a diameter of 8 mm was cast into a mold. The prepared test piece was stretched at room temperature with a stroke of 6 mm / min using Type 5966 manufactured by Instron, and the strength when the test piece was broken was measured. In the present invention, when the tensile strength is 84 MPa or more, it is a strength that is not a problem in practical use, and therefore, it is evaluated as "0", and when it is less than 84 MPa, it is evaluated as "×".

[0095] Table 1 shows the evaluation results.

[0096] (3) Thermal fatigue resistance

[0097] (3-1) Preparation of solder paste

[0098] A solder paste was prepared by mixing a flux prepared from 42 parts by mass of rosin, 35 parts by mass of a glycol solvent, 8 parts by mass of a thixotropic agent, 10 parts by mass of an organic acid, 2 parts by mass of an amine, and 3 parts by mass of a halogen with a solder powder having a size (particle size distribution) of No. 4 in the classification of powder size in JIS Z 3284-1:2014 (Table 2) and made of an alloy composition of Example 1, Example 8, Comparative Example 3, Comparative Example 8, or Comparative Example 10 in Table 1. The mass ratio of the flux to the solder powder was flux:solder powder=11:89.

[0099] (3-2) Preparation and evaluation of evaluation samples

[0100] like Figure 1 As shown, the solder (solder paste) was applied on the DCB as the base material, and the terminals (external connection terminals) with L-shaped cross sections were soldered to prepare two evaluation samples. The external connection terminals were clamped and fixed with bolts in a chuck tool, and evaluated using a tensile testing machine. The evaluation conditions were as follows: the test load was 300N in the tensile direction, the test speed was 3mm / min, and the tensile test was repeated in an atmosphere of 125°C.

[0101] For the average value of the number of repeated stretches until fracture, the alloy composition of Comparative Example 10 in Table 1 was used as the judgment standard. If it was 3 times or more of the average value of the number of stretches using the alloy composition, it was evaluated as "0", which was a level without practical problems, and if it was less than 3 times, it was evaluated as "×". The evaluation results are shown in Table 2.

[0102] [Table 1]

[0103]

[0104] The underline indicates that the invention is outside the protection scope.

[0105] [Table 2]

[0106]

[0107] The underline indicates that the content is outside the protection scope of the present invention.

[0108] It is clearly confirmed from Tables 1 and 2 that the Ag, Cu and Bi of Examples 1 to 8 are all in the optimal range. Therefore, since the liquidus temperature is low enough to allow soldering in step soldering and the solidus temperature is not too low, the installation is excellent. It is further confirmed that a high tensile strength is exhibited. It is known that in Examples 1, 3, 4, 6 and 8 that satisfy Formulas (1) to (3), in particular, the liquidus temperature is further low, and the tensile strength further exhibits a high value exceeding 90 MPa. In addition, it is known that the number of repeated stretchings until fracture of Examples 1 and 8 is at a level that is not a problem in practical use. The repeated tensile strength until fracture of the other Examples is also at a level that is not a problem in practical use.

[0109] On the other hand, the Ag content of Comparative Example 1 is high, so the liquidus temperature is high and the tensile strength is poor. The Ag content of Comparative Examples 2 and 3 is low, so the liquidus temperature is high and the tensile strength is poor. In addition, Comparative Example 3 immediately broke during the repeated tensile test.

[0110] Comparative Examples 4, 8, and 9 have high liquidus temperatures due to high Cu contents, while Comparative Example 5 has high liquidus temperatures due to low Cu contents and poor tensile strength.

[0111] Comparative Example 6 has a high Bi content, so the solidus temperature is low. Comparative Example 7 has a low Bi content, so the liquidus temperature is high and the tensile strength is poor. In addition, Comparative Example 7 immediately broke during the repeated tensile test.

[0112] Comparative Example 10 has a low Cu content and contains no Bi, so both the solidus temperature and the liquidus temperature are high and the tensile strength is poor. In addition, Comparative Example 10 immediately breaks during the repeated tensile test.

Claims

1. A solder paste, characterized in that: It has solder powder formed of a solder alloy and a flux, The solder alloy comprises, by mass%, 2.0 to 4.0% Ag, 0.51 to 0.79% Cu, more than 4.0% Bi and less than 7.9% Bi, with the remainder consisting only of Sn, the alloy composition satisfies the following equations (1) and (2), the solder alloy has a solidus temperature of 197° C. or higher and a liquidus temperature of less than 217° C., and a tensile strength of 84 MPa or higher. 10.9≤Sn / Bi≤22.4 (1) 61.2≤Sn×Cu≤64.6 (2) In the above formulas (1) and (2), Sn, Bi and Cu represent the contents (mass %) of the respective alloy compositions.

2. The solder paste according to claim 1, wherein The solder alloy satisfies the following formula (3): 45.50≤Sn×Ag≤365 (3) In the above formula (3), Sn and Ag represent the contents (mass %) of the respective alloy compositions.

3. A solder joint comprising a solder alloy constituting the solder paste according to claim 1 or 2.

Citation Information

Patent Citations

  • Low toxity alloy composition for bonding and sealing

    JP1990070033A

  • Electronic component and manufacturing method

    JP2004122223A

  • Solder alloy and on-vehicle electronic circuit

    JP2019155466A